Media Pembelajaran Online Dalam Pembentukan Karakter Akademik Di UPT SMP Negeri 1 Suppa Kabupaten Pinrang - Riska Cahayani; Abd. Halik; Usman Noer; Herdah Herdah; Marhani Marhani (Journal on Education, 2025)
Education is the most important thing in a person's life, which means that every human being has the right to receive a proper education. Learning design starts from analytical activities that are used to describe real learning problems that need to be found for solutions. Online learning is a process of mastering material either on the internet or participating in online teaching and learning activities using electronic devices connected to the internet.This research is a type of qualitative research, namely the research used is based on the scientific conditions of the research object that occur in the field. This research is descriptive qualitative, which is a form of research aimed at describing existing phenomena and facts using an ex post facto approach.The findings of this study reveal that the design of Online learning design, namely RPP (Learning Implementation Plan) using the WhatsApp application and the Zoom application. This was expressed by teachers and students that online learning in the formation of students' academic character is still not optimal in the learning process. The principal and teachers at UPT SMP Negeri 1 Suppa, Pinrang Regency have provided online learning during the Covid-19 pandemic, students were less than optimal in carrying out the online learning process, and students preferred face-to-face learning.